2004
DOI: 10.1023/b:prev.0000023082.00109.87
|View full text |Cite
|
Sign up to set email alerts
|

Tijuana Alcohol Control Policies: A Response to Cross-Border High-Risk Drinking by Young Americans

Abstract: Several thousand young Americans visit the bars in Tijuana, Mexico, each weekend night, raising concerns on both sides of the border. Measures implemented in San Diego, California, and Tijuana have successfully reduced the number of American visitors to Mexican bars. Although San Diego policies have been well-documented, this is the first article on investigation of measures enacted south of the border. Information on Tijuana alcohol policies was obtained from a survey of 29-36 bars from 1997 to 1999. The Tiju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Along these border communities there are bars that actively promote heavy consumption to underage drinkers (12). Romano and associates (13) indicated that bars in Mexico attempt to attract customers by displaying drink discounts such as ''All You Can Drink'' or themed nights as ''College Night,'' that offers single drinks priced as low as 25 cents each.…”
mentioning
confidence: 99%
“…Along these border communities there are bars that actively promote heavy consumption to underage drinkers (12). Romano and associates (13) indicated that bars in Mexico attempt to attract customers by displaying drink discounts such as ''All You Can Drink'' or themed nights as ''College Night,'' that offers single drinks priced as low as 25 cents each.…”
mentioning
confidence: 99%
“…The population of Tijuana-San Diego experience a broad range of social and health related problems, which have a major impact on both sides of the border [11][12][13][14]. There is a continuum of issues which cuts right across the political, regional, and social infrastructure, right down to the level of the individual, in a recursive manner.…”
Section: Problems With Interpretation Of Mas Simulationsmentioning
confidence: 99%
“…Hispanics tend to be particularly at risk of drinking and driving near the border with Mexico (McKinnon, O'Rourke, Thompson, & Berumen, 2004). The minimum legal drinking age in Mexico is 18, and bars in Mexican border towns cater to American youth, who are encouraged to drink heavily by offers of low prices and tolerance of drunken behavior Lange, Lauer, & Voas, 1999;Romano et al, 2004, Kelley Baker, Johnson, Voas, & Lange, 2000. Research has revealed that, on weekend evenings, thousands of youth (20 and younger) and young adults (21 to 25) residing in communities along the U.S. border go to Mexico to patronize all-night bars .…”
Section: G Rural/urban Settingsmentioning
confidence: 99%
“…[Latino] high school kids cross the border to go to bars." Because the negative effect of this weekend night drinking at Mexican bars spans across both young Latino and White border crossers, to be effective, strategies to deter heavy drinking by American visitors to Mexico should incorporate measures tailored to each of these groups (Romano et al, 2004).…”
Section: G Rural/urban Settingsmentioning
confidence: 99%